AFFIXATION, REDUPLICATION IN DESCRIPTION TEXT OF THAILAND EXCHANGED STUDENTS - agus Sulaeman (STIBA IEC JAKARTA, 2019)
The purpose of this research is to describe the form of affixation interference and reduplication of Indonesian language in description text of Thailand exchanged students who learned Indonesian Language in Indonesian Education and Literature department (PBSI), University of Muhammadiyah Tangerang. This study used a qualitative approach with content analysis research method which aimed to explain and interpret the data systematically, thoroughly, and the relationship between the events investigated. The content analysis is a method which is conducted by making inference contextually. The sources of data related to this research language and Literature is morphological interference in description text of Thailand exchanged students learned in UMT. The data collection techniques were gained by observation and document studies. The document study was in from the students’ description text. The result of this research is assumed to be very important since the affixation interference must be handled as early as possible, especially in the world of interference education. Interference is a violation in Indonesian language. How to prevent the spread of interference is to conduct research that occurs in the world of education and fix it as early as possible.